Manager–Employee Gender Congruence and the Bureaucratic Accountability of Public Service Employees: Evidence From Schools. (December 2016) - Pedersen, Mogens Jin; Nielsen, Vibeke Lehmann
Much theory suggests that manager–employee gender congruence (that manager and employee share the same gender) may influence employee accountability. This article empirically tests this notion by examining how manager–employee gender congruence among public service employees relates to two key aspects of bureaucratic accountability: (a) organizational goal alignment and (b) compliance with organizational rules and regulations. Using school fixed effects on teacher survey data and administrative school data, we find that male teachers with male principals are less aligned with their school's goals and less compliant with its rules and regulations than are male teachers with female principals.